2018
DOI: 10.4103/sjg.sjg_490_17
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and outcome of inflammatory bowel diseases in children in Saudi Arabia: A single-center experience

Abstract: Background/Aim:Inflammatory bowel disease (IBD) is a chronic gastrointestinal disorder which includes ulcerative colitis (UC), Crohn's disease (CD), and indeterminate colitis (IC). The natural history of pediatric IBDs is poorly understood and generally unpredictable. We aim to study the natural history of IBD in Saudi children including the extraintestinal manifestations, changes in diagnosis, disease behavior, medical management, and surgical outcome.Patients and Methods:A retrospective review of all the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, only 5% of CD patients have dermatological manifestations, 15.5% have arthritis or arthralgia, and 2.3% have deep vein thrombosis (DVT) [ 20 ]. A study in Riyadh showed that 32% of pediatric IBD patients have EIMs, most of them have indeterminate colitis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only 5% of CD patients have dermatological manifestations, 15.5% have arthritis or arthralgia, and 2.3% have deep vein thrombosis (DVT) [ 20 ]. A study in Riyadh showed that 32% of pediatric IBD patients have EIMs, most of them have indeterminate colitis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…I presume that the differences in the reported prevalence and pattern of EIMs in the study by Alreheili et al . [ 1 ] and that reported in other Saudi studies[ 2 3 ] could be plausibly explained by a number of factors.…”
mentioning
confidence: 77%
“…I refer to the interesting study by Alreheili et al . [ 1 ] published in this Journal. It is well-known that inflammatory bowel disease (IBD) is associated with a variety of extraintestinal manifestations (EIMs) that could produce greater morbidity than the underlying intestinal disease and might even be the initial presentation of IBD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] A study conducted in Riyadh, Saudi Arabia, reported an even higher EIM prevalence among pediatric IBD patients (32%), the majority with indeterminate colitis. [ 12 ] In a South Korean study, frequent EIMs in IBD patients included rheumatoid arthritis, aphthous stomatitis, and osteoporosis. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%